1986
DOI: 10.1002/j.1460-2075.1986.tb04341.x
|View full text |Cite
|
Sign up to set email alerts
|

Second gene (nif H* ) coding for a nitrogenase iron protein in Azotobacter chroococcum is adjacent to a gene coding for a ferredoxin-like protein

Abstract: Azotobacter chroococcum MCD1 contains a cluster of nitrogen fixation (nif) genes coding for the structural polypeptides for nitrogenase (nifH for the Fe‐protein and nifD and nifK for the MoFe protein) and a second sequence in the genome homologous to nifH. DNA fragments bearing this second nifH‐like sequence were cloned and the DNA sequence around the homologous region determined. Two open reading frames were identified in this region. One codes for a protein of 289 amino acid residues and is highly homologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…chroococcum since a strain deleted for the nifHDK cluster was still capable of fixing N 2 in molybdenum-deficient medium (Robson, 1986). This is consistent with the presence of nzfH*, coding for a second nitrogenase Fe-protein (Robson et al, 1986a), and a second nifK-like sequence in the genome of this organism (Robson, 1986). N, fixation in the deletion strain depends upon vanadium and is catalysed by a two-component nitrogenase complex with a typical Fe-protein (component 2) but in which the conventional molybdoprotein (component 1) is replaced by a vanadoprotein.…”
Section: E V a N S A N D O T H E R Ssupporting
confidence: 72%
See 1 more Smart Citation
“…chroococcum since a strain deleted for the nifHDK cluster was still capable of fixing N 2 in molybdenum-deficient medium (Robson, 1986). This is consistent with the presence of nzfH*, coding for a second nitrogenase Fe-protein (Robson et al, 1986a), and a second nifK-like sequence in the genome of this organism (Robson, 1986). N, fixation in the deletion strain depends upon vanadium and is catalysed by a two-component nitrogenase complex with a typical Fe-protein (component 2) but in which the conventional molybdoprotein (component 1) is replaced by a vanadoprotein.…”
Section: E V a N S A N D O T H E R Ssupporting
confidence: 72%
“…The relationship at the genetic level between the Mo-and V-based Nz fixation systems is particularly interesting. Considering the broad similarities in the two sets of nitrogenase proteins (Robson et al, 1986a;Robson, 1986) it is probable that the two systems have arisen from one or more gene duplication events. Not all genes may be duplicated; some may be common to both systems, others unique to each system.…”
Section: E V a N S A N D O T H E R S Discussionmentioning
confidence: 99%
“…The genetic basis of the V nitrogenase from A. vinelandii is not as well understood as it is for the V nitrogenase from A. chroococcum, but extensive similarities appear to exist within the two organisms (49, 55; our unpublished results). The vnfH genes in both organisms are organized in an operon also containing a ferredoxin-like gene downstream from vnfH (28,54). The vnJfl-ferredoxin operon is separated from an operon containing the structural genes (vnfD vnfK) for dinitrogenase 2 by approximately 2 kilobase pairs (kbp) in A. chroococcum and by 1 kbp in A. vinelandii (55 and our unpublished results).…”
mentioning
confidence: 79%
“…promoter sequence (2) 1079 3115 GGG CGG GTT GGC ACT ATC AAC CCC ATC TTT ACC TGT CAA CCG G R V G T I N P I F T C Q P 3157 GCC GGT GCC CAG TTC GTC AGT ATC GGT ATC AAG GAT TGC ATC A G A Q F V S I G I K D C I 3199 GGT ATC GTG CAT GGC GGC CAA GGC TGC GTG ATG TTC GTC CGC (54), and of nifH3 from Clostridium pasteurever, the highest degree of similarity exists between the ianum (66) is shown in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
“…The target of ADP-ribosylation is not only conserved in dinitrogenase reductases of the ' conventional' molybdenum nitrogenase but also in the corresponding proteins of alternative nitrogen fixation systems (Robson et al, 1986;Joerger et al, 1989;Schuddekopf et al, 1993) and it has been shown that the alternative nitrogenase of R. rubrurn is also modified by DraT (Lehman & Roberts, 1991a). The photosynthetic non-sulphur purple bacterium Rhodobacter capsulatus also contains two nitrogenase systems : the molybdenum nitrogenase (encoded by nifHDK) and an alternative heterometal-free (' irononly ') nitrogenase (anfHDGK; Schneider et al, 199 1 b ;Gollan et al, 1993;Schuddekopf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%